Evaluation of the psychometric performance of the SCOFF questionnaire in a Mexican young adult sample Evaluación del desempeño psicométrico del cuestionario SCOFF en una muestra de adultos jóvenes mexicanos - Omar Sánchez-Armass; Flavia Cristina Drumond-Andrade; Angela R Wiley; Marcela Raffaelli; Celia Aradillas-García (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To examine the psychometric performance of the SCOFF, a brief screening instrument for eating disorders (ED). MATERIALS AND METHODS: Mexican university applicants (n= 3594, 55.7% female, M age= 18.1 years) completed self-report measures and a health screen. RESULTS: Confirmatory factor analyses revealed one factor for females. However a bifactor model fits better for males and females. Reliability was lower for females (KR20 = .49) than males (KR20 = .59). More females (24.2%) presented risk for ED (SCOFF > 2) than males (11.2%). Nomological validity indicated that risk for ED in young women was associated with demographic (e.g., parental education), psychological (e.g., depression, weight management efficacy), physical (e.g., BMI), and social (e.g., family conflict) indicators in conceptually coherent ways. Fewer variables were significant for males. CONCLUSION: Although the SCOFF may be a useful ED screen in Mexico, further research must examine its criterion validity, sensitivity, and specificity. OBJETIVO: Examinar el desempeño psicométrico del SCOFF, un instrumento de tamizaje para trastornos de conducta alimentaria (TCA). MATERIAL Y MÉTODOS: Aspirantes mexicanos a una universidad (n = 3594, 55.7% mujeres, edad M = 18.1 años) completaron cuestionarios y una revisión médica. RESULTADOS: Análisis factoriales confirmatorios revelaron un factor para mujeres, aunque un modelo bifactorial funcionó mejor para hombres y mujeres. La fiabilidad fue menor en mujeres (KR20= .49) que en hombres (KR20= .59). Las mujeres (24.2%) presentaron mayor riesgo de TCA (SCOFF > 2) que hombres (11.2%). Validez nomológica indicó que el riesgo de TCA en mujeres jóvenes estuvo asociado con indicadores demográficos (e.g., educación paterna), psicológicos (e.g., depresión, control eficaz de peso), físicos (e.g., IMC), y sociales (e.g., conflicto familiar) de forma conceptualmente coherente. Un subconjunto de estas variables fueron significativas para los hombres. CONCLUSIÓN: El SCOFF podría ser un tamizaje de TCA útil en México. Sin embargo, se requiere más investigación sobre su validez de criterio, sensibilidad y especificidad.